Writing a wrong: Coupled RNA polymerase II transcription and RNA quality control. (7th March 2019) - Peck, Sarah A.; Hughes, Katlyn D.; Victorino, Jose F.; Mosley, Amber L.
Abstract : Processing and maturation of precursor RNA species is coupled to RNA polymerase II transcription. Co‐transcriptional RNA processing helps to ensure efficient and proper capping, splicing, and 3′ end processing of different RNA species to help ensure quality control of the transcriptome. Many improperly processed transcripts are not exported from the nucleus, are restricted to the site of transcription, and are in some cases degraded, which helps to limit any possibility of aberrant RNA causing harm to cellular health. These critical quality control pathways are regulated by the highly dynamic protein–protein interaction network at the site of transcription. Recent work has further revealed the extent to which the processes of transcription and RNA processing and quality control are integrated, and how critically their coupling relies upon the dynamic protein interactions that take place co‐transcriptionally. This review focuses specifically on the intricate balance between 3′ end processing and RNA decay during transcription termination. This article is categorized under: RNA Turnover and Surveillance > Turnover/Surveillance Mechanisms RNA Processing > 3' End Processing RNA Processing > Splicing Mechanisms RNA Processing > Capping and 5' End Modifications Abstract : Dynamic coupling of RNAPII transcription complex and RNA processing machinery is the first‐line of defense for nuclear RNA quality control.